Astronomical Perspective in Determining the Traditional Daling System Of The Nias Tribe in Bawodobara Village - Hadiani Fitri; Retno Kaldianus (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
The Traditional Nias Calendar in Bawodobara Village refers to a Moon cycle or Moon phases consisting of the first 15 days called the bright Moon and the last 15 days the dark Moon, this calendar system is classified as a lunisolar calendar with astronomical calculations. In addition to using the phases of the Moon and Sun, the Nias people use the Star Orion to determine the seasons each year (Sara Wangahalö). This study aims to (1) understand the Nias tribe's calendar system in Bawodobara Village from an astronomical perspective and (2) determine why the Nias Bawodobara community uses a calendar system. This study used a qualitative approach with descriptive analysis. Data collection methods and sources include documentation, interviews, and observations. This data analysis uses three stages: data reduction, data presentation, and drawing conclusions. This study shows that the Nias Tribe Calendar in Bawodobara Village uses celestial bodies such as the Moon and Sun phases as a reference for the changing seasons. The calendar from the perspective of astronomy helps the Nias people carry out daily activities such as farming, raising livestock, cooking, eating, and sleeping schedules. The Calendar System in the Nias Tribe in Bawodobara Village has the names of the months in the traditional Nias language, so that it becomes a characteristic and unique feature of the Nias Tribe Calendar System.